The impact of laboratory findings and optical coherence tomography biomarkers on response to intravitreal anti-VEGF treatment in patients with retinal vein occlusion - Chatziralli, I; Kazantzis,D.; Kroupis, C.; Machairoudia,G.; Dimitriou, E.; Theodossiadis, G; Theodossiadis, P; Sergentanis, T.N. (Int.Ophthalmol., 2022)
AIMS: To investigate potential laboratory and imaging biomarkers as treatment response predictors to intravitreal anti-vascular endothelial growth factor (anti-VEGF) agents in patients with retinal vein occlusion (RVO). METHODS: Participants in this prospective study were 53 patients with treatment naive macular edema secondary to RVO, treated with intravitreal anti-VEGF agents and followed-up for 12 months. At baseline, all participants underwent best-corrected visual acuity measurement, dilated fundoscopy, optical coherence tomography and fluorescein angiography (FFA), while full blood count and biochemical analysis of various parameters was also performed. At month 12, treatment response was examined and classified as "favorable" or "non-response". Potential associations between laboratory/imaging biomarkers and treatment response were assessed. RESULTS: Univariate analysis showed that "favorable" response at month 12 after initiation of anti-VEGF treatment was correlated with baseline central subfield thickness (CST) < 464 mum (p < 0.001), absence of subretinal fluid (p = 0.004), absence of hyperreflective foci (HF) (p = 0.004), intact ellipsoid zone (EZ) and external limiting membrane (ELM) (p < 0.001 and p = 0.001, respectively), absence of epiretinal membrane (ERM) (p = 0.020) and absence of macular ischemia on FFA (p < 0.001), while increased monocytes-to-lymphocytes ratio was also associated with "favorable" treatment response (p = 0.010). All other laboratory parameters did not reach statistical significance. However, at the multivariate analysis, EZ and ELM status, HF, macular ischemia and monocytes-to-lymphocytes ratio were found to be independent predictors of treatment response. CONCLUSIONS: Intact EZ and ELM, absence of HF, absence of macular ischemia and increased monocytes-to-lymphocytes ratio at baseline can predict "favorable" treatment response in patients with treatment naive macular edema secondary to RVO
Keywords: Angiogenesis Inhibitors; antagonists & inhibitors; Bevacizumab; Biomarkers; Blood; Complications; Diagnosis; Drug Therapy; Etiology; Humans; Intravitreal Injections; Ischemia; Macular Edema; methods; Prospective Studies; Retinal Vein Occlusion; Retrospective Studies; therapeutic use; Tomography,Optical Coherence; Vascular Endothelial Growth Factor A; Visual Acuity